KAJIAN POTENSI MANUSIA DAN BENTANG ALAM TERHADAP REKONSILIASI KEHIDUPAN SOSIAL BERBASIS MANAJEMEN EKONOMI KAWASAN DAS CITARUM KECAMATAN RENGASDENGKLOK KABUPATEN KARAWANG - Sumbogo, Ignatius Ario; Dara, Siti Ruhana (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This research is structured in order to measure the potential impact of human resources and natural resources potentiality on the socio-economic quality of life index in the Citarum River Basin area, as well as constructing its impact on the formulation of the strategy of a social life reconciliation program that stirs regional economic development. Design/methodology/approach- This research uses a field research method with a qualitative approach, in which data collection and data processing techniques using the technique triangulation and source triangulation. Findings-The results showed several findings, first, the potential of HR is quite low which correlates with the decline in the quality of socioeconomic life. Second, the availability of natural resources has the potential to support regional economic development. Third, there are obstacles in the regional management system, at any various levels, i.e. individual, organizational, and government institution level. Fourth, tourism-based area revitalization is the key strategy for regional economic development. The revitalization of tourism-based zones, supported by the historical, cultural, and natural potentiality, is a key recommendation point for stakeholders, both at the local, provincial, and central levels. Keywords: human resources, natural resources, social reconciliation, tourism-based development, socio-economic index